2014
DOI: 10.1177/1350650114556398
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-hydrodynamics of couple stress lubricants in combined squeeze and shear in parallel annular disc viscous coupling systems

Abstract: This paper presents predictive analysis of load carrying capacity, tractive efficiency and response time of parallel annular discs intervened with a film of lubricant under combined shear and squeeze film motions. This configuration represents operational characteristics of viscous coupling systems. In particular, the case of viscous dampers for tractive torque generation and distribution in all-wheel-drive off-road vehicles is studied. Various forms of lubricant behaviour, from idealised Newtonian to that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…As the value of "Hm" approaches zero, Equation (9) reduces to the Reynolds equation (i.e., non-conducting electrical lubricant), with lubricant considered to behave as Newtonian fluid. Table 2 presents operating parameters which have been selected from available literature (Lin et al, 2013;Daliri et al, 2015) for the present work. A steady state lubricant film pressure distribution is achieved by a coupled solution of different governing Equations (9, 12, 13, 14, and 16) satisfying the (a) Lubricant rheological properties (Lin, 2010;Daliri et al, 2015) Physical quantity Symbol Numerical value of physical quantity Dowson and Higginson (1966) and Hamrock and Jacobson (1984) Dimensionless load W 2×10 −5 − 7 × 10 −5…”
Section: Resultsmentioning
confidence: 99%
“…As the value of "Hm" approaches zero, Equation (9) reduces to the Reynolds equation (i.e., non-conducting electrical lubricant), with lubricant considered to behave as Newtonian fluid. Table 2 presents operating parameters which have been selected from available literature (Lin et al, 2013;Daliri et al, 2015) for the present work. A steady state lubricant film pressure distribution is achieved by a coupled solution of different governing Equations (9, 12, 13, 14, and 16) satisfying the (a) Lubricant rheological properties (Lin, 2010;Daliri et al, 2015) Physical quantity Symbol Numerical value of physical quantity Dowson and Higginson (1966) and Hamrock and Jacobson (1984) Dimensionless load W 2×10 −5 − 7 × 10 −5…”
Section: Resultsmentioning
confidence: 99%
“…Upper plate squeezing motion will lead to v � 0 at z � h and w � dh/dt. Equations (1) and (2) will lead to the velocity components of u and v under the boundary conditions described in (7) and 8:…”
Section: Governing Equationsmentioning
confidence: 99%
“…ey also showed that magnetohydrodynamic couple stress fluids perform better in a steady load rather than a transient load conditions. For lubricated parallel annular discs, combined with squeeze film and shear motions, Daliri et al [7] showed that contact load-carrying capacity increases by the presence of magnetohydrodynamic couple stress fluids. For the same geometry of parallel annular plates, however, increased rotational inertia can diminish the squeeze film characteristics [8].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies in the field of couple stress lubricants can be found elsewhere [17][18][19][20]. Also, fluid flow in rotating discs has been investigated by other researchers [20][21][22][23][24][25][26]. However, according to the earlier studies reviewed above, investigation of squeeze film characteristics between two parallel annular discs considering effects of couple stress fluid and viscosity-pressure dependency together with considering rotational inertial effects have not been a topic of investigation.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, Lin et al [16] studied the effects of viscositypressure dependency on the non-Newtonian squeeze film characteristics between parallel circular plates. Other studies in the field of couple stress lubricants can be found elsewhere [17][18][19][20]. Also, fluid flow in rotating discs has been investigated by other researchers [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%